Incorporating social and environmental indicators in technical and economic advisory programmes in livestock farming - Arandia A.; Intxaurrandieta J.M.; Mangado J.M.; Santamaría P.; Icaran C.; Lopez E.; Del Hierro O.; Pinto M.; Ruiz R.; Nafarrate L. (Economic, social and environmental sustainability in sheep and goat production systems, 2011)
The impact that agricultural policies exert on the sustainability and multifunctional nature of farming systems, together with the huge amount of scientific references available, has been central to the implementation of this work. The main objectives of the project were: (i) to broaden the scope of the existing farmers' advisory programmes from a technical and economic perspective to social and environmental issues; and (ii) to develop a decision support tool able to cope with the three pillars of sustainability within the framework of the holistic analysis of livestock farming systems. For this purpose, a set of economic, environmental and social indicators has been proposed and a computer tool developed to manage the database, to calculate the value of every indicator, to assess each livestock farm, and to generate graphic outputs.
7. Proceedings of the International Seminar of the Sub-Network on Production Systems of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2010/11/10-12, Zaragoza (Spain)